Energy consumption, economic growth and environmental degradation in OECD countries - Ozcan, Burcu; Tzeremes, Panayiotis G.; Tzeremes, Nickolaos G. (Elsevier, 2020)
The interdependence among energy consumption, economic growth and environmental degradation has become an important public policy priority among OECD countries. Yet, the related literature provides conflicting results when describing the dynamic nature of such a relationship and the way it affects countries' development path. Using a sample of 35 OECD countries over the period 2000-2014, we find that economic growth and energy consumption patterns contribute to the enhancement of countries' environmental performance levels. In contrast to a large stream of empirical research, our findings highlight that countries' economic development path and their energy consumption patterns have started to align with their environmental policies. The results are robust since we utilize different aspects of countries' environmental degradation such as carbon dioxide emissions, ecological footprints and countries' environmental performance levels. Finally, the analysis of the dynamic interrelations among countries' energy consumption, economic growth and environmental degradation levels, reveals the necessity to promote sustainable development through a coexistence rather than through a trade-off mechanism.
Keywords: Economic growth; Energy consumption; Environmental degradation; Panel vector autoregressive models; OECD countries